Staphylococcus Aureus Tames Nociceptive Neurons to Suppress Synovial Macrophage Responses for Sustained Infection in Septic Arthritis - Xinyu Fang; Yang Chen; Haiqi Ding; Changyu Huang; Hongxin Hu; Chaofan Zhang; Yunzhi Lin; Qijin Wang; Xueni Hu; Yiming Lin; Yongfa Chen; Nanxin Zhang; et al. (Advanced Science)
Abstract The interaction between the nervous system and immune system during chronic bacterial infection remains unclear. Here, it is reported that Staphylococcus aureus (S. aureus) infection induces calcitonin gene‐related peptide (CGRP) secretion from intra‐articular transient receptor potential cation channel subfamily V member 1 positive (TRPV1+) nociceptive nerves through its pore‐forming toxin (PFT) α‐hemolysin. The released CGRP then inhibits the production of chemotactic cytokines by CX3CR1+ tissue‐resident synovial lining macrophages via receptor activity modifying protein 1 (RAMP1) receptors at the onset of septic arthritis. During the subsequent chronic course of infection, the continuous release of CGRP triggered by pain has a lasting effect on the antimicrobial capabilities of macrophages, thereby promoting bacterial survival and joint damage. This evidence suggests a critical role for neuroimmune regulation in S. aureus‐induced chronic septic arthritis. CGRP receptor antagonism may reduce joint destruction, thus providing a new option for treating bone and joint infections.